ANALISIS STRATEGI KUALITAS PELAYANAN UNTUK MENINGKATKAN KEPUASAN NASABAH PADA AXA MANDIRI INSURANCE CABANG A.YANI BANJARMASIN - Nor Annisa; Husnurrofiq; Apriya Santi (Jurnal Ilmiah Ekonomi Bisnis, 2019)
This study aims to: (1) Analyze whether service quality in the form of reliability, responsiveness, empathy, beliefs and direct evidence simultaneously affect customer satisfaction. (2) Analyzing whether service quality in the form of reliability, responsiveness, empathy, beliefs and direct evidence partially influences customer satisfaction. (3) Analyze the most dominant variables that affect customer satisfaction. With the purposive sampling method, there were 50 respondents. The analytical method used is multiple linear regression.The results of this study are: (1) Service quality in the form of reliability, responsiveness, empathy, beliefs and direct evidence simultaneously affected customer satisfaction by 44.7% while the remaining 55.3% was influenced by other variables. (2) Only empathy and belief that have a partial effect on customer satisfaction, while reliability, responsiveness and direct evidence have no partial effect on customer satisfaction. (3) Reliability is not a variable that has a dominant influence on customer satisfaction at AXA Mandiri Branch A. Yani Banjarmasin.